BALANCING ACT: CHALLENGES AND STRATEGIES IN INTEGRATED EDUCATION MANAGEMENT - Hasan, Arikunto (Top Journal of Public Policy and Administration (TJPPA), 2023)
Education as a fundamental human right is enshrined in the legal framework of Indonesia, as articulated in Law Number 39 of 1999. This law emphasizes the importance of personal development, access to education, self-improvement, and an enhanced quality of life for every individual, aligning with the principles of human rights. However, despite these legal provisions, the realization of universal education in Indonesia, particularly in remote and underprivileged regions, remains a challenge. One of the key initiatives aimed at addressing the disparities in education quality and accessibility is the nine-year compulsory education program. While this program has noble intentions, it has not achieved its full potential. There continues to be a significant gap in the quality of education, particularly between urban and rural areas, with a specific focus on the 3T regions (outermost, lagging, frontier). These areas face unique challenges in providing equitable educational opportunities. To bridge this gap, the Indonesian government has introduced integrated education programs for elementary and junior high schools in these underserved regions. Integrated schools represent a novel educational model where teaching and learning activities occur in a single location. This model is designed to bring educational institutions closer to communities, mitigating issues related to distant school locations and improving access for students. Nevertheless, the challenges in remote and underdeveloped regions persist. These difficulties include the placement of qualified teachers, establishing standard educational facilities, addressing communication barriers, and ensuring an adequate supply of teaching aids. Moreover, the stringent requirements of the national curriculum and standardized education systems hinder the 3T and border regions' ability to catch up with the rest of the country in terms of educational attainment. This paper explores the multifaceted challenges facing the implementation of integrated education programs in 3T regions and border areas of Indonesia. It delves into the persistent issues related to teacher placement, infrastructure development, and curriculum adaptation. By examining these challenges, the study aims to provide insights into the obstacles preventing the equitable delivery of education in these regions and proposes potential solutions.